2010
DOI: 10.1093/dnares/dsq021
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Two-Component Systems and Prediction of Stress-Responsive Two-Component System Members in Soybean

Abstract: In plants, the two-component systems (TCSs) play important roles in regulating diverse biological processes, including responses to environmental stress stimuli. Within the soybean genome, the TCSs consist of at least 21 histidine kinases, 13 authentic and pseudo-phosphotransfers and 18 type-A, 15 type-B, 3 type-C and 11 pseudo-response regulator proteins. Structural and phylogenetic analyses of soybean TCS members with their Arabidopsis and rice counterparts revealed similar architecture of their TCSs. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(126 citation statements)
references
References 97 publications
7
116
0
3
Order By: Relevance
“…No additional families of response regulators were found unique to rice or Arabidopsis. These results confirm and expand on previous analyses (Pareek et al, 2006;Pils and Heyl, 2009;Mochida et al, 2010), with minor differences likely due to our analyses being performed on a larger complement of signaling elements and/or being based on the conserved domains rather than the entire sequence.…”
Section: Phylogenetic Relationship Of Two-component Signaling Elementsupporting
confidence: 89%
“…No additional families of response regulators were found unique to rice or Arabidopsis. These results confirm and expand on previous analyses (Pareek et al, 2006;Pils and Heyl, 2009;Mochida et al, 2010), with minor differences likely due to our analyses being performed on a larger complement of signaling elements and/or being based on the conserved domains rather than the entire sequence.…”
Section: Phylogenetic Relationship Of Two-component Signaling Elementsupporting
confidence: 89%
“…Protein sequences of all known plant TCS genes, particularly 56, 52, 51, 98, 62, and 85 members in the genome of Arabidopsis , rice, maize, soybean, Lotus japonicus , Physcomitrella patens , wheat, and Chinese cabbage, respectively, were downloaded from Phytozome [44] and then used as queries to perform BLASTP searches in the SGN database () with E -value of 1 × 10 −5 as the threshold [9,30]. Meanwhile, the tomato genome protein sequences were downloaded from SGN database and Hidden Markov Model (HMM) profiles of TCS characteristic domains, i.e., HisK (PF00512), HATPase (PF02518), HPt (PF01627), and REC (PF00072) were downloaded from Pfam ().…”
Section: Methodsmentioning
confidence: 99%
“…Although the subcellular localization of these AHPs is independent of CK and CK-receptor AHKs (14), AHP gene expression is induced by CK (15,16). All five AHPs, as well as those in rice and soybean, contain a consensus sequence of HQXKGSSXS with a highly conserved His residue (17,18). Analyses of ahp multiple mutants indicated that with the exception of AHP4, for which consistent evidence is lacking, all remaining AHPs function as redundant positive regulators of CK signaling and affect many aspects of plant development (13).…”
mentioning
confidence: 99%